MOTIVASI AUTHOR CHANBAEKSHIPPER DALAM MENGGUNAKAN WATTPAD - Marista, Aulia; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium; Vol 1 No 2 (2019), 2019)
ABSTRACT Wattpad is a social media including social media category with the main characteristics of the social networking site is user-generated-content. New media give rise to participatory culture, w hichis participatory culture is an example of fan culture or fandom, where fans not only consume but also produce and distribute. Like fans who are author Chanbaekshipper, which is OTP fandom with slash pairing using Wattpad to process media content fandom (fanfiction). This research aims to identify and explain the motivation author Chanbaekshipper in using Wattpad. The method used is descriptive method which is a qualitative research. T he r esults from this study is that there are couple of motivation author chanbaekshipper in using Wattpad, interpersonal utility, passtime, information seeking, convenience and entertainment. Author chanbaekshipper not only act as  producers who produces fanfiction but they also consumers who consume and a disributor who distributes the fanfiction that they created Wattpad. Keywords: Motivation, Fan Culture, Participatory Culture, Social Media Wattpad